Extra-Cerebellar Signs and Non-motor Features in Chinese Patients With Spinocerebellar Ataxia Type 3 - Yuan, Xiaoqin; Ou, Ruwei; Hou, Yanbing; Chen, Xueping; Cao, Bei; Hu, Xun; Shang, Huifang (Frontiers in Neurology, 2019)
Objectives: Our study attempts to systematically explore the prevalence of extra-cerebellar signs and non-motor symptoms such as anxiety, depression, fatigue, excessive daytime sleepiness (EDS) and sleep disturbances in a cohort of Chinese patients with spinocerebellar ataxia type 3 (SCA3), and further to investigate the correlations between non-motor symptoms and clinical characteristics in SCA3 patients. Methods: This study included 68 molecular-proven SCA3 patients. Extra-cerebellar signs were evaluated with the Inventory of Non-Ataxia Symptoms (INAS). The INAS count indicated the number of non-ataxia signs in each patient. The severity of ataxia, fatigue, EDS, sleep quality, anxiety and depression were assessed by using Scale for the assessment and rating of ataxia (SARA), Fatigue Severity Scale (FSS), Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Rating Scale (HAMA) and Hamilton Depression Rating Scale (HAMD) (24 items), respectively. Results: Extra-cerebellar signs were detected in 91.2% of all SCA3 patients and the mean total INAS count was 2.72±1.88. Rigidity was the most frequent extra-cerebellar sign (47.1%, N=32). Sensory symptoms (2.9%, N=2) and chorea (5.9%, N=4) were rare, and myoclonus (0%) was not found in this cohort. A high frequency of sleep disturbances (64.7%), fatigue (52.9%), depression (48.5%) and anxiety (42.6%) were detected in SCA3 patients. The HAMD score was associated with CAG repeats and HAMA score. The PSQI score was correlated with SARA and FSS score. What's more, multiple linear regression analysis showed that CAG repeats, age of onset, sleep disturbances and depression were significant predictors of fatigue in SCA3 patients. Conclusions: Our study indicates that the vast majority of SCA3 patients present with extra-cerebellar signs. Except for EDS, anxiety, depression, fatigue and impaired sleep quality are prevent in SCA3 patients. CAG repeats, age of onset, sleep disturbances and depression are predictors of fatigue in SCA3 patients.